Research on(t,k)-diagnosability for exchanged hypercube network - Xi XIONG; Jia-rong LIANG; Qiang MA (Tongxin xuebao)
Fault diagnosis was an important part in the processing of network system repair.PMC was a diagnosis model which was simple and easy to be understood.Through analysis of the structure of exchanged hypercube,a generalization measure of fault diagnosis for the network system was provided,called (t,k)-fault diagnosis method.By computing,it is shown that EH(s,p) is ( 2 s + p − 1 2 , s + 1 ) -diagnosable and conditional ( 2 s + p + 1 − 2 s p + 1 , 2 s ) -diagnosable,where 1≤s≤p.The result shows that the(t,k)-diagnosability of EH(s,p) is 2 s + p − 1 2 ,which is bigger than its ordinary diagnosability s+1,and the conditional (t,k)-diagnosability is 2 s + p + 1 − 2 s p + 1 ,which is bigger than its ordinary conditional diagnosability 4s-3.Above results present the important theory basis for fault diagnosis of exchanged hypercube network.